Assessing dolomite surface reactivity at temperatures from 40 to 120 °C by hydrothermal atomic force microscopy. (15th February 2017) - Berninger, Ulf-Niklas; Saldi, Giuseppe D.; Jordan, Guntram; Schott, Jacques; Oelkers, Eric H.
Abstract: This study investigated the reactivity of the (1 0 4) dolomite surface in the system MgCO3 –CaCO3 –NaCl–H2 O via a suite of aqueous solution–dolomite hydrothermal atomic force microscopy interaction experiments at temperatures from 40 to 120 °C, pH ranging from 4 to 8, pressures up to 5 bars, and over a wide range of aqueous fluid saturation state. Dolomite dissolution was observed in the presence of undersaturated aqueous fluids. Dissolution produced crystallographically well defined etch pits, consistent with the stoichiometric release of ordered lattice cations. In low to moderately saturated fluids, dolomite growth began by the growth of one or two layers of carbonate (layer height <3 Å) which morphologically reproduced the initial surface features, resembling the template effect as previously described by Astilleros et al. (2003, 2006) and Freij et al. (2004). Further growth was strongly inhibited and did not show any systematic crystallographically orientated growth morphologies. At aqueous fluid saturation states exceeding 500, nucleation and growth was observed on the dolomite surfaces at moderate rates, but these did not exhibit the characteristic dolomite crystallographic orientation after the growth of several layers. Taken together these observations suggest that the direct precipitation of dolomite from aqueous solution is disfavored at temperatures to at least 120 °C due to the poisoning of the dolomite surface for further growth by the precipitation of one to four Ca–Mg carbonate layers on these surfaces.